Discussions on Stakeholder Requirements for Space Weather‐Related Models. Issue 4 (30th April 2018) - Shprits, Yuri Y.; Zhelavskaya, Irina S.; Green, Janet C.; Pulkkinen, Antti A.; Horne, Richard B.; Pitchford, David; O'Brien, T. Paul; Glover, Alexi
Abstract: Participants of the 2017 European Space Weather Week in Ostend, Belgium, discussed the stakeholder requirements for space weather‐related models. It was emphasized that stakeholders show an increased interest in space weather‐related models. Participants of the meeting discussed particular prediction indicators that can provide first‐order estimates of the impact of space weather on engineering systems. Key Points: Stakeholders need a clear and simple input that they can easily use and understand Early warning will allow stakeholders to start preparations for mitigation procedures Simple indicators tuned to stakeholder needs can be used